(untitled) (Research, Society and Development, 2026)
Calcium hydroxyapatite (CaHA) is a widely used biostimulator in orofacial harmonization, especially for its ability to stimulate collagen production and promote skin rejuvenation. However, its use is not without risks and complications, making in-depth knowledge essential for professionals to avoid serious adverse effects. This study aims to review the main risks and complications related to the use of calcium hydroxyapatite in aesthetics, emphasizing its safety, indications, contraindications, and management methods. An integrative literature review was conducted using indexed databases available in English and Portuguese. The review revealed that, despite the proven efficacy of CaHA as a biostimulator, its application requires careful planning, anatomical knowledge, and technical expertise. Complications can range from mild events, such as erythema and edema, to serious occurrences, such as persistent nodules, tissue necrosis, and risk of blindness due to vascular occlusion. The use of facial ultrasound has been considered an important tool in the prevention and early diagnosis of complications. Furthermore, proper management — especially in cases of necrosis — requires rapid interventions, which may include the use of anti-inflammatory drugs, vasodilators, warm compresses, and, in some cases, antibiotics or surgical interventions. It is concluded that the safe use of calcium hydroxyapatite depends directly on the professional’s training, knowledge of facial anatomy, and respect for technical contraindications. Understanding and preventing possible complications are essential to ensure satisfactory results and preserve the health and safety of patients.